2013
DOI: 10.1590/s0100-40422013000700007
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization-cracking of n-octane on catalysts based on heteropolyacid H3Pw12O40 and heteropolyacid supported on zirconia and promoted with Pt and Cs

Abstract: Recebido em 10/9/12; aceito em 1/3/13; publicado na web em 4/6/13Isomerization-cracking of n-octane was studied using H 3 PW 12 O 40 (HPA) and HPA supported on zirconia and promoted with Pt and Cs. The addition of Pt and Cs to the supported HPA did not modify the Keggin structure. The Pt addition to the supported HPA did not substantially modify the total acidity; however, the Brönsted acidity increased significantly. Cs increased the total acidity and Brönsted acidity. A linear relation was observed between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Various articles have been published on HPA catalyzing the cracking and isomerization of hydrocarbons, but they deal almost exclusively with hydrocarbons having C‐numbers equal to or below 10 . Attention has also been paid to acidic cesium salts of phosphotungstic acid like Cs 2.5 H 0.5 PW 12 O 40 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various articles have been published on HPA catalyzing the cracking and isomerization of hydrocarbons, but they deal almost exclusively with hydrocarbons having C‐numbers equal to or below 10 . Attention has also been paid to acidic cesium salts of phosphotungstic acid like Cs 2.5 H 0.5 PW 12 O 40 .…”
Section: Introductionmentioning
confidence: 99%
“…), and catalytic activity can be linked very well to surface acidity for several reactions . Furthermore, cesium phosphotungstates can act as carriers for catalytically active transition metals such as platinum, palladium, and nickel , , , .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the heteropoly acids, which have been used successfully as superacid catalysts in different chemical reactions, would be candidates as a Brønsted acid site for the isomerization reaction. The delocalization of the negative charge on the large anion of a heteropoly acid enables its protons to easily participate in the isomerization reaction . As a consequence, we observed that, under the same test conditions, the activity of Pt/HPMo‐Y catalyst was higher than the Pt/Y catalyst.…”
Section: Resultsmentioning
confidence: 73%
“…The adequacy and significance of the second‐order quadratic model was evaluated using an analysis of variance (ANOVA), and the results of the statistical analysis are represented in Table . The fitted model was significant because of the very low probability value ( P model < .0001) and high F‐value of the model ( F model = 30.32) at a confidence level of 95% . Therefore, the prediction of the iso‐alkane yield based on the regression model was suitable.…”
Section: Resultsmentioning
confidence: 99%